Urban Environment and Infrastructure : Toward Livable Cities - Bigio, Anthony G.; Dahiya, Bharat (Washington, DC: World Bank, 2013)
This review of the active portfolio of World Bank projects aimed at improving urban environmental quality was carried out during 2002-03 in order to assess the level of commitment of the institution to urban sustainability. The review focuses on the contributions of key sectors to urban environmental improvements, in particular on those belonging to the Infrastructure Vice-Presidency, and on how projects are contributing to achievement of the Millennium Development Goals. It also highlights some of the apparent gaps in current Bank lending in regional, spatial, and thematic terms and argues for a more comprehensive and holistic approach to urban environmental priorities, which could lead to better-integrated investments. The Bank corporate strategy on urban development (World Bank 2000a) addresses the urban environment as part of enhancing urban livability. The corporate environment strategy (World Bank 2001b) states its importance through its goals of improving the quality of life, improving the quality of growth, and protecting the quality of regional and global commons.